Dynamics of carbon sources supporting burial in seagrass sediments under increasing anthropogenic pressure. (15th March 2017) - Mazarrasa, Inés; Marbà, Núria; Garcia‐Orellana, Jordi; Masqué, Pere; Arias‐Ortiz, Ariane; Duarte, Carlos M.
Abstract: Seagrass meadows are strong coastal carbon sinks of autochthonous and allochthonous carbon. The aim of this study was to assess the effect of coastal anthropogenic pressure on the variability of carbon sources in seagrass carbon sinks during the last 150 yr. We did so by examining the composition of the sediment organic carbon (Corg ) stocks by measuring the δ 13 Corg signature and C : N ratio in 210 Pb dated sediments of 11 Posidonia oceanica seagrass meadows around the Balearic Islands (Spain, Western Mediterranean) under different levels of human pressure. On average, the top meter sediment carbon deposits were mainly (59% ± 12%) composed by P. oceanica derived carbon whereas seston contribution was generally lower (41% ± 8%). The contribution of P. oceanica to the total sediment carbon stock was the highest (∼ 80%) in the most pristine sites whereas the sestonic contribution was the highest (∼ 40–80%) in the meadows located in areas under moderate to very high human pressure. Furthermore, an increase in the contribution of sestonic carbon and a decrease in that of seagrass derived carbon toward present was observed in most of the meadows examined, coincident with the onset of the tourism industry development and coastal urbanization in the region. Our results demonstrate a general increase of total carbon accumulation rate in P. oceanica sediments during the last century, mainly driven by the increase in sestonic Corg carbon burial, which may have important implications in the long‐term carbon sink capacity of the seagrass meadows in the region examined.